SCLEROMYXEDEMA WITH RETINAL VASCULITIS AND MACULAR EDEMA. Issue Volume 11:Issues 4(2017:Autumn) (2017) - Gutiérrez-Aguirre, Karen I.; Stewart, Michael W.; Sluzevich, Jason C.
Abstract : Background/Purpose: To describe the findings and clinical course of a patient with scleromyxedema complicated by retinal vasculitis and macular edema. Methods: Interventional case report. Results: A 64-year old Caucasian woman with recently diagnosed, biopsy proven scleromyxedema presented with decreased visual acuity (20/50 OD; 20/100 OS) due to retinal vasculitis and macular edema. She received intravitreal bevacizumab and subtenon's triamcinolone acetonide for the macular edema, and bilateral pars plana vitrectomies were required for vitreous hemorrhages. Monthly intravenous infusions of immunoglobulins (IVIG) resulted in resolution of the macular edema and vasculitis, and stabilization of the VA (20/40 OD; counting fingers at 6 feet OS). Conclusion: Scleromyxedema may be complicated by retinal vasculitis and macular edema. Treatment with corticosteroids and vascular endothelial growth factor inhibitors may be minimally effective but IVIG should be considered for both the ocular and systemic findings. Abstract : A 64-year-old woman with scleromyxedema presented with retinal vasculitis and macular edema. Subtenon's triamcinolone and intravitreal bevacizumab appeared to be ineffective, but the ocular findings improved after monthly intravenous infusions of immunoglobulins.